Interest and Academic Performance in Physics of Grade 10 Students amidst Pandemic - Donna A. Villaceran; Joji D. Linaugo; Joel M. Bual (Journal of Education Reseach and Evaluation, 2024)
Students' interest is significant in their academic performance in Physics. However, due to the pandemic, their interest and performance results still need to be higher. Therefore, this study analyzed the interests and academic achievements of 10th-grade physics students and compared them by gender. This study also investigates significant differences in their academic interests and achievements when grouped by gender. This research uses a quantitative design with a descriptive, comparative, and correlational approach. The research subjects were 108 Class 10 Physics students determined using convenience sampling. Data collection methods use questionnaires and tests. The data collection instruments are questionnaire sheets and test questions. The statistical tools used in data analysis are mean, standard deviation, Mann-Whitney U Test, and Spearman Rank Correlation. The research results show that students are generally interested in physics and do not meet expectations in terms of academic achievement. Meanwhile, there is no difference in their academic interests and achievements when grouped by gender. However, there is a significant relationship between their interests and academic performance. Given the results, continuous improvement in content delivery, teaching strategies, and assessments is necessary to ensure student interest and academic performance.